Sweet Taste Receptor Serves to Activate Glucose- and Leptin-Responsive Neurons in the Hypothalamic Arcuate Nucleus and Participates in Glucose Responsiveness - Kohno, Daisuke; Koike, Miho; Ninomiya, Yuzo; Kojima, Itaru; Kitamura, Tadahiro; Yada, Toshihiko (Frontiers in Neuroscience, 2016)
The hypothalamic feeding center plays an important role in energy homeostasis. In the feeding center, whole-body energy signals including hormones and nutrients are sensed, processed, and integrated. As a result, food intake and energy expenditure are regulated. Two types of glucose-sensing neurons exist in the hypothalamic arcuate nucleus (ARC): glucose-excited neurons and glucose-inhibited neurons. While some molecules are known to be related to glucose sensing in the hypothalamus, the mechanism underlying glucose sensing in the hypothalamus are not fully understood. The sweet taste receptor is a heterodimer of taste type 1 receptor 2 (T1R2) and taste type 1 receptor 3 (T1R3) and senses sweet tastes. T1R2 and T1R3 receptors are distributed in multiple organs including the tongue, pancreas, adipose tissue, and hypothalamus. However, the role of sweet taste receptors in the ARC remains to be clarified. To examine the role of sweet taste receptors in the ARC, cytosolic Ca2+ concentration ([Ca2+]i) in isolated single ARC neurons were measured using Fura-2 fluorescent imaging. An artificial sweetener, sucralose at 10-5 M-10-2 M dose dependently increased [Ca2+]i in 12-16% of ARC neurons. The sucralose-induced [Ca2+]i increase was suppressed by a sweet taste receptor inhibitor, gurmarin. The sucralose-induced [Ca2+]i increase was inhibited under an extracellular Ca2+-free condition and in the presence of an L-type Ca2+ channel blocker, nitrendipine. Sucralose-responding neurons were activated by high-concentration of glucose. This response to glucose was markedly suppressed by gurmarin. More than half of sucralose-responding neurons were activated by leptin but not ghrelin. Percentage of proopiomelanocortin (POMC) neurons among sucralose-responding neurons and sweet taste receptor expressing neurons were low, suggesting that majority of sucralose-responding neurons are non-POMC neurons. These data suggest that sweet taste receptor-mediated cellular activation mainly occurs on non-POMC leptin-responding neurons and contributes to glucose responding. Endogenous sweet molecules including glucose may regulate energy homeostasis through sweet taste receptors on glucose-and leptin-responsive neurons in the ARC.